Local self-government audit reporting in selected Balkan countries: a comparative content analysis of supreme audit institutions' reports - Ivan Dionisijev; Zorica Bozhinovska Lazarevska; Todor Tocev; Bojan Malchev (Journal of Public Budgeting, Accounting & Financial Management, 2026)
Purpose This study evaluates the transparency and reporting practices of local self-government (LSG) audit reporting across four Supreme Audit Institutions (SAIs), North Macedonia, Montenegro, Croatia and Slovenia, over the period 2015–2024. It examines how SAIs communicate municipal audit results, the extent to which reporting practices align with internationally recognized accountability principles and how differences in institutional contexts are associated with variation in reporting patterns. Design/methodology/approach The study employs a longitudinal comparative content analysis of 40 annual reports, operationalised through a novel Local Audit Transparency Index (LATI) comprising four dimensions: structure and visibility, audit scope and findings, follow-up and implementation, and accessibility and transparency. Binary scoring and theory-informed interpretation (principal–agent, accountability neo-institutionalism) are used to analyze cross-country differences. Findings The results reveal significant heterogeneity in LSG audit reporting practices. North Macedonia, Slovenia, and Croatia attain similarly high LATI scores, though with different profiles: North Macedonia demonstrates consistent structural visibility and accessibility; Slovenia exhibits comprehensive coverage across scope-related indicators; and Croatia records full indicator coverage in the follow-up dimension in the final years. Montenegro shows comparatively lower LATI scores, with reporting focused on individual municipal audit excerpts and limited disclosure of follow-up information. Research limitations/implications The study is limited to publicly available annual reporting practices and does not assess individual audit reports, internal SAI procedures or causal institutional determinants. Future research should integrate interview-based evidence, link LATI scores to objective municipal financial outcomes and extend the framework to additional EU and non-EU SAIs to examine broader applicability. Originality/value This study offers the first decade-long, multi-country evaluation of LSG audit reporting practices in the Western Balkans. It introduces the LATI as an operational framework for assessing audit transparency in subnational audit reporting and translates abstract accountability concepts into observable empirical indicators. The analysis provides comparative evidence on how reporting patterns differ across institutional context and highlights variation in follow-up disclosure at the municipal level.